Combustion - Glassman, Irvin (Academic Press, 1996)
This Third Edition of Glassman's classic text clearly defines the role of chemistry, physics, and fluid mechanics as applied to the complex topic of combustion. Glassman's insightful introductory text emphasizes underlying physical and chemical principles, and encompasses engine technology, fire safety, materials synthesis, detonation phenomena, hydrocarbon fuel oxidation mechanisms, and environmental considerations. Combustion has been rewritten to integrate the text, figures, and appendixes, detailing available combustion codes, making it not only an excellent introductory text but also an i.